Diseño del complejo turístico “RIO AGUARICO”, mediante la elaboración del plan de negocios, para fortalecer el turismo en el Cantón Lago Agrio, Provincia de Sucumbíos - Ullauri Salgado, Johana Victoria (2018)
Nueva Loja is a town that was born in the 70s with the oil boom; It is a city in whose streets you admire a sample of the country's diversity, as its people migrated from several provinces, especially from Loja, Manabí and El Oro. Its official name is Nueva Loja and the traditional one, Lago Agrio, the same as loses among the legends and jokes of its inhabitants. Among its main tourist attractions is the La Perla Park, spas in the Aguarico River, the Pyramids, San Miguel International Bridge, Bay Lagoon, Blue Lagoon, Loma Linda, Little Mermaid, the Cabin, Atari Community Center, Central Park, Children's Park , La Madre Park, Simón Bolívar Park, Lago Agrio Lagoon, Yanakucha Lagoon and ancestral villages such as the Kichwas. That is why it is necessary to implement business ideas to meet the needs of tourists who like to enjoy nature. Therefore, a study has been carried out for the implementation of a Tourist Complex, which will provide recreational, lodging and food services. In order to carry out the present work, we used methods that allowed the development of the research in an orderly and sequential manner, within these we have: inductive, deductive, analytical, historical-logical and statistical, likewise techniques were used, such as the bibliographic review and the survey, which allowed the collection of primary and secondary information. The results of the different studies such as the market, technical, economic-financial and financial evaluation showed positive results, so that investors can analyze and decide on its implementation. The financial evaluation project the following results: The net present value that is $ .391.796.99, which is a positive value and greater than the investment, the Internal Rate of Return that is 21.29% that is greater than the opportunity cost of the 9%, the Benefit / Cost Ratio, which is 1.16 US dollars for each dollar invested, the investment will be recovered in 4 years, 9 months and 22 days; the project supports an increase in costs of 46.4% and a decrease in revenues of 22%. Therefore, as there are positive results, investors are recommended to implement the project, thus contributing to the socioeconomic development of the canton, province and country, as well as improving the living standards of the inhabitants of the sector.